Humor Techniques of Netizens Comment on Instagram: A Semantics Analysis - Haloho, Besti Horasia; Saragih, Silvia Efani; Simanjuntak, Windy Octalin; Sidauruk, Eunike; Dian Marisha Putri (Talenta Publisher, 2023)
Humor is definitely the thing that makes people laugh. Humor can be seen anywhere, directly or indirectly, on TV or social media. The aim of the study is to analyze the humor techniques found in comments on video posts that are currently viral in Indonesia. This study is conducted using a qualitative method and Berger's technical theory of humor. This study uses one technical category from the four technical categories discovered by Berger, namely technical language. The language techniques consist of ridicule, infantilism, bombast, puns, sarcasm, irony, satire, misunderstanding, repartee, outwitting, and sexual allusions. The data about humor was collected based on comments from diverse users of Instagram, specifically those followed by the study's primary author.